Products of Idempotent Operators - Arias, Maria Laura (2017)
The goal of this article is to study the set of all products EF with E, F idempotent operators defined on a Hilbert space. We present characterizations of this set in terms of operator ranges, Hilbert space decompositions and generalized inverses.